The importance of psychological messages and the “questionbehavior effect” about remdesivir - Matos, Aloisio Antonio Gomes de; Oliveira, Séphora Natércia Albuquerque; Rolim Neto, Modesto Leite (Avanços em Medicina, 2025)
Background: The FDA has been requiring that information about using remdesivir to treat COVID-19 be made available to healthcare providers and patients, including dosing instructions, potential side effects, and drug interactions. It is important to observe the initial indicators of anxiety, fear, and euphoria for families during emergencies, including information on the possible side effects. This situational context is very important in all the world, because it opens doors for providing the use of updated information about treatment follow-up and for offering improved mental health services.Method: The studies were identified in well-known international journals found in two electronic databases: Scopus and Embase. The data were cross-checked with information from the main international newspapers.Results: The high expectations supported by an immediate discourse culminate in frustration and displeasure, while more consistent empirical results are not generated. These two are predictors of psychic suffering, especially due to the scarcity of information and uncertainties. In parallel, recent studies indicate that spreading information without scientific basis intensifies damage to the routine and health of people, which are already impacted by the pandemic situation. This misrepresented spread may be a factor for unleashing fear and, as a consequence, social despair.Conclusions: Based on the impulsive scenarios stimulated in the context of hydroxychloroquine and on the high spread of fake or distorted news, the psychiatric impacts of COVID-19 pandemic associated with the use of remdesivir may be worsened and reflected directly on the population’s self-esteem.